Increased prevalence of premature coronary atherosclerosis after preeclampsia. (14th October 2021) - Hauge, M G; Damm, P; Kofoed, K F; Ersboell, A S; Johansen, M; Sigvardsen, P E; Fuchs, A; Kuhl, J T; Nordestgaard, B G; Koeber, L; Gustafsson, F; Linde, J J
Abstract: Background: Women with preeclampsia have increased risk of manifest coronary artery disease later in life. However, it remains unknown if and when premature coronary atherosclerotic stages can be identified. This knowledge could enable early intervention in women considered at high risk for future manifest coronary artery disease. Purpose: Using cardiac computed tomography, we aimed to investigate the prevalence of premature coronary atherosclerosis in women with previous preeclampsia in comparison with women from the general population. Methods: Women, aged 40–55 years, with previous preeclampsia were recruited in the CPH-PRECIOUS study and compared 1:1 with age- and parity-matched women from the CGPS. Both groups underwent a cardiac computed tomography, including a contrast-enhanced coronary computed tomography angiography and a non-contrast coronary artery calcium scoring, as well as an overall assessment of cardiovascular risk factors imbedded in an extensive questionnaire. Cardiac computed tomography examinations were analysed blindly. The main outcome of the study was the prevalence of any coronary atherosclerosis defined as any plaque at coronary computed tomography angiography or a calcium score >0 in case of a non-diagnostic coronary computed tomography angiography. Results: A total of 1, 424 women were included (715 women with previous preeclampsia and 709 controls from the general population). Women with previous preeclampsia were more likely to have cardiovascular risk factors (hypertension, dyslipidaemia, diabetes mellitus). The prevalence of any coronary atherosclerosis was significantly higher in the preeclampsia group (27.4% vs. 20.0%) (P=0.001). A calcium score >0 was also more prevalent in the preeclampsia group (16.6% vs. 11.8%) (P=0.009). Preeclampsia remained an independent risk factor for the presence of any coronary atherosclerosis after adjusting for cardiovascular risk factors (age, hypertension, dyslipidaemia, diabetes, smoking, body mass index, parity) (OR=1.37, 95% CI (1.05–1.79), P=0.021). Conclusion: Women with previous preeclampsia are more likely show premature signs of coronary atherosclerosis compared with an age- and parity matched control group from the general population. Preeclampsia is an independent risk factor for premature coronary atherosclerosis. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The Danish Heart FoundationSkibsreder Per Henriksen, R og Hustrus FondKong Christian den Tiendes FondBrødrene Hartmanns FondHans og Nora Buchards FondArvid Nilssons FondAnita og Tage Therkelsens FondLægefondenAase og Ejnar Danielsens FondHjertecentrets Forskningsudvalg (Rigshospitalet)Direktør Kurt Bønnelycke og Hustru Fru Grethe Bønnelyckes FondLægeforeningens ForskningsfondTorben & Alice Frimodt FondHenry og Astrid Møllers Fond